Gamifying water crisis management: A serious game for drinking water contamination emergency response. - Jingyan Huang; Catherine M Ashcraft; Weiwei Mo (PLoS ONE)
This paper presents a serious game that simulates a water crisis triggered by the spill of an unregulated chemical. The game includes five stakeholder roles representing a chemical manufacturer, resident, water treatment plant, environmental agency, and health department, in addition to a facilitator role. The game seeks to provide players with practical experience of the communication and collaboration needed among different stakeholders to prepare for and respond to water contamination emergencies. Initial findings from game sessions with 41 participants suggest that frequent, proactive, and transparent communication can expedite the decision-making process and resolve the crisis more effectively. The game results also reveal challenges in inter-organizational coordination and communication, highlighting the need for training and standardized communication terminologies and protocols.